2017
DOI: 10.1016/j.biortech.2017.02.032
|View full text |Cite
|
Sign up to set email alerts
|

Formic acid aided hot water extraction of hemicellulose from European silver birch ( Betula pendula ) sawdust

Abstract: Hemicellulose has been extracted from birch (Betula pendula) sawdust by formic acid aided hot water extraction. The maximum amount of hemicellulose extracted was about 70mol% of the total hemicellulose content at 170°C, measured as the combined yield of xylose and furfural. Lower temperatures (130 and 140°C) favored hemicellulose hydrolysis rather than cellulose hydrolysis, even though the total hemicellulose yield was less than at 170°C. It was found that formic acid greatly increased the hydrolysis of hemice… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
9
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
3

Relationship

1
9

Authors

Journals

citations
Cited by 44 publications
(11 citation statements)
references
References 29 publications
0
9
1
Order By: Relevance
“…With the 30% formic acid solution, the hemicellulose sugar yields increased only slightly, from 50 to 55%, and the total glucose yields from 10 to 14%, when the reaction time increased from 1 to 2 h. With the 15% acid solution, similar increase in yields was observed; however, the hemicellulose sugar yield was somewhat higher (61%), and the total glucose yield slightly lower (13%) after 2 h than with 30% acid. The hemicellulose sugar yields achieved in this study with formic acid were clearly better than the xylose yield reported in the literature (41%), in which 14.52 wt% formic acid was used as an extraction medium for silver birch sawdust at 140°C with a 2-h reaction time [34].…”
Section: Formic Acidcontrasting
confidence: 72%
“…With the 30% formic acid solution, the hemicellulose sugar yields increased only slightly, from 50 to 55%, and the total glucose yields from 10 to 14%, when the reaction time increased from 1 to 2 h. With the 15% acid solution, similar increase in yields was observed; however, the hemicellulose sugar yield was somewhat higher (61%), and the total glucose yield slightly lower (13%) after 2 h than with 30% acid. The hemicellulose sugar yields achieved in this study with formic acid were clearly better than the xylose yield reported in the literature (41%), in which 14.52 wt% formic acid was used as an extraction medium for silver birch sawdust at 140°C with a 2-h reaction time [34].…”
Section: Formic Acidcontrasting
confidence: 72%
“…Hemicellulose has been extracted by many different methods, i.e., chemical (Jiang et al 2014;Zhang et al 2016;Liu et al 2018), physical (Chandra et al 2015), biological (Kaur et al 2016;Zhou et al 2020), and combined pretreatments (Amidon and Liu 2009). Hydrothermal pretreatment is one of the main physical pretreatment methods (Zhuang et al 2016;Goldmann et al 2017). It has the advantages of low energy consumption, low requirement for chemical substances, little influence on physicochemical structure, and high recovery rate of hemicellulose (Yao et al 2015(Yao et al , 2017Ge et al 2020).…”
Section: Introductionmentioning
confidence: 99%
“…Several methods, such as alkali treatment, 9 acid treatment, 10 organic solvents treatment, 11 and use of sub- or supercritical technology, 12 have been proposed to extract lignin from lignocellulosic biomass. In the development of lignin extraction process from lignocellulosic biomass, the major concerns are to find the source of lignin, which possesses negligible economical values, to find a suitable solvent to dissolve and decompose biomass, and to design a process with low energy consumption and less complexity.…”
Section: Introductionmentioning
confidence: 99%